The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1128/iai.72.7.4114-4126.2004
|View full text |Cite
|
Sign up to set email alerts
|

Description of the Transcriptomes of Immune Response-Activated Hemocytes from the Mosquito Vectors Aedes aegypti and Armigeres subalbatus

Abstract: Mosquito-borne diseases, including dengue, malaria, and lymphatic filariasis, exact a devastating toll on global health and economics, killing or debilitating millions every year (54). Mosquito innate immune responses are at the forefront of concerted research efforts aimed at defining potential target genes that could be manipulated to engineer pathogen resistance in vector populations. We aimed to describe the pivotal role that circulating blood cells (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
121
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(125 citation statements)
references
References 58 publications
(75 reference statements)
1
121
0
2
Order By: Relevance
“…17 In mosquitoes of the genera Anopheles and Armigeres, FBG-like proteins have been implicated in immune responses to microbes or malaria parasites because their transcript levels are up-regulated after infection. [19][20][21][22][23] Sialic-acid-binding lectins which contain FBG domains have been identified from the slug Limax flavus and found to be down-regulated after parasitism. 25 With respect to human ficolins, which are the best-studied FBG-bearing proteins in terms of structure and function, three types of ficolins (L-, H-, and M-ficolin) have lectin activity and can activate the lectin complement pathway.…”
Section: Discussionmentioning
confidence: 99%
“…17 In mosquitoes of the genera Anopheles and Armigeres, FBG-like proteins have been implicated in immune responses to microbes or malaria parasites because their transcript levels are up-regulated after infection. [19][20][21][22][23] Sialic-acid-binding lectins which contain FBG domains have been identified from the slug Limax flavus and found to be down-regulated after parasitism. 25 With respect to human ficolins, which are the best-studied FBG-bearing proteins in terms of structure and function, three types of ficolins (L-, H-, and M-ficolin) have lectin activity and can activate the lectin complement pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Besides viral infection, a number of apoptosis-related genes, as well as other immune response genes, are expressed in hemocytes of Ae. aegypti and Armigeres subalbatus infected with bacterial pathogens (Bartholomay et al, 2004). In addition, Plasmodium can elicit pathology resembling apoptosis in mosquito vectors.…”
Section: Introductionmentioning
confidence: 99%
“…Despite its similarity across many taxa, Hsc70 is diverse in its functions (Takei & Haucke, 2001;Zhao et al, 2009). In the mosquito Aedes aegypti, Hsc70 isoform B is differentially expressed in response to treatment with heat shock (Nirdé et al, 2010); however, it was identified in an immune response-activated haemocyte library derived from the mosquito Armigeres subalbatus (Bartholomay et al, 2004). The increased expression of Hsc70 has also been shown in Anopheles gambiae when infected by the o'nyong-nyong virus (ONNV) (Sim et al, 2005).…”
Section: Discussionmentioning
confidence: 97%